2015
DOI: 10.1044/2015_ajslp-14-0105
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Recasts in Language Intervention: A Systematic Review and Meta-Analysis

Abstract: Purpose This systematic review and meta-analysis critically evaluated the research evidence on the effectiveness of conversational recasts on grammatical development for children with language impairments. Method Two different but complementary reviews were conducted and then integrated. Systematic searches of the literature resulted in 35 articles for the systematic review. Studies that employed a wide variety of study designs were involved but all examined interventions where recasts were the key component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 68 publications
(144 reference statements)
2
78
1
7
Order By: Relevance
“…For example, if a child leaves off the copula be from their speech and says, “The dog running,” a clinician might respond with the correct form by saying, “Yes, the dog is running very fast.” A recent meta-analysis by Cleave, Becker, Curran, Van Horne, and Fey (2015) supports the use of recasting in intervention. The present study supports a basic assumption inherent to recasting, namely, that children can learn accurate forms from what they hear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if a child leaves off the copula be from their speech and says, “The dog running,” a clinician might respond with the correct form by saying, “Yes, the dog is running very fast.” A recent meta-analysis by Cleave, Becker, Curran, Van Horne, and Fey (2015) supports the use of recasting in intervention. The present study supports a basic assumption inherent to recasting, namely, that children can learn accurate forms from what they hear.…”
Section: Discussionmentioning
confidence: 99%
“…Cleave, Becker, Curran, Van Horne, & Fey, 2015). Several treatment studies reported in the language intervention literature provide evidence that supports the basic efficacy of conversational recast treatment for targeting morphosyntax in preschool-age children (e.g., Camarata & Nelson, 1992;Camarata, Nelson, & Camarata, 1994;Leonard, Camarata, Brown, & Camarata, 2004;Leonard, Camarata, Pawlowska, Brown, & Camarata, 2006;Nelson, Camarata, Welsh, Butkovsky, & Camarata, 1996).…”
Section: Conversational Recast Treatmentmentioning
confidence: 99%
“…Multiple studies using versions of conversational recast therapy have resulted in significant improvements in children's grammatical skills (see Cleave et al, 2015, for a review). Enhanced conversational recast treatment, as used by Plante et al (2014), yielded positive gains in use of morphology by preschool children with SLI.…”
Section: Discussionmentioning
confidence: 99%
“…Given that both groups of children share grammatical deficits, approaches that have been successful for children with SLI might also be useful for children with cochlear implants. Conversational recast is one treatment technique that has been used successfully to treat morpheme deficits in children with SLI (see Cleave, Becker, Curran, Owen Van Horne, & Fey, 2015, or McCauley & Fey, 2006 for reviews). Conversational recast treatment does not involve explicit instruction of targeted grammatical forms, but rather provides verbal models of at least one grammatical form (e.g., auxiliary is, plural s) that is the target of treatment.…”
Section: Discussionmentioning
confidence: 99%